2020
DOI: 10.1017/s0885715620000536
|View full text |Cite|
|
Sign up to set email alerts
|

CRL optics and silicon drift detector for P06 Microprobe experiments at 35 keV

Abstract: A provisional setup for X-ray microprobe experiments at 35 keV is described. It is based on compound refractive lenses (CRLs) for nanofocusing and a Vortex silicon drift detector with 2 mm sensor thickness for increased sensitivity at high energies. The Microprobe experiment (PETRA III) generally uses Kirkpatrick-Baez mirrors for submicrometer focusing in the energy range of 5–21 keV. However, various types of scanning X-ray microscopy experiments require higher excitation energies. The CRL optics were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Further improvements towards lower dose or higher sensitivity can easily be achieved by an upgraded experimental setup, mainly increasing the number of detectors. Additionally, silicon drift detectors with larger thicknesses have become commercially available recently 33 , promising to increase the efficiency at 28 keV up to a factor of four. By reducing the footprint of our imaging cell, we expect to be able to halve the detector distance.…”
Section: Discussionmentioning
confidence: 99%
“…Further improvements towards lower dose or higher sensitivity can easily be achieved by an upgraded experimental setup, mainly increasing the number of detectors. Additionally, silicon drift detectors with larger thicknesses have become commercially available recently 33 , promising to increase the efficiency at 28 keV up to a factor of four. By reducing the footprint of our imaging cell, we expect to be able to halve the detector distance.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a reduction of scan times by at least a factor of ten is readily feasible for 'fly scan' capable positioners. Furthermore, it has already been demonstrated that focal spot sizes of down to 110 nm are achievable by utilizing phase plates for aberration corrections at 15 keV (Ossig et al, 2021), as well as at 35 keV (Falkenberg et al, 2020), at P06. Spatial resolution on the nanoscale should be enabled by the nominal angular resolution below 0.1 mrad and the nominal translation resolution of 1 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Compound refractive lenses (CRLs) were used to focus the beam to a spot size of 2.0 mm  1.2 mm, which was measured by knife-edge scans of crossed gold wires. The focal distance of the CRLs was 660 mm measured from the pinhole exit (0.4 mm diameter) of the N 2 -rinsed CRL box, which leads to a longitudinal spot size of a few millimetres and a photon flux above 10 9 at the focal position (Falkenberg et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…XRF measurements were performed at the microhutch endstation of the P06 beamline (Fig. 2) at Petra III in Hamburg, Germany 13 . A double crystal monochromator (DCM) was used to select an incident photon energy of 12 keV, which was 2/6 just above the K absorption edge of As (11.9 keV).…”
Section: Plaque Samplesmentioning
confidence: 99%